Analysis and experimental verification of multi-band thin monopole antennas loaded with half-mode CRLH-inspired resonators. Issue 13 (2nd September 2018) - Abdalla, Mahmoud A.; Hu, Zhirun
Abstract: This paper presents analysis and experimental measurements of CPW and microstrip compact monopole antennas loaded with resonator circuits inspired from simplified half-mode composite right / left-handed unit cell. The antennas were designed to have a typical omnidirectional radiation pattern. The CPW fed dual-band antenna resonates at 2.4 and 5.8 GHz, respectively. The antenna size is 20 × 30 mm 2 and the radiator patch is only 25% at 2.4 GHz and 60% 5.8 GHz in comparison with a conventional patch antenna. The microstrip triple-band antenna covers the frequency bands from 2 to 2.4 GHz, 5.4 to 6 GHz and 6.8 to 8 GHz. The antenna size is 28 × 25 mm 2 which is less than 25% at lower frequency band compared to the size of the conventional patch antenna. Detailed theoretical and full-wave analysis is presented and experimental results demonstrate a good agreement between the measured and the simulated. The suggested antennas can be employed for compact size and multi-band functionalities in wireless applications. The loading technique can be adapted for more frequency bands.